Cost‐effectiveness analysis of integrating screening and treatment of selected non‐communicable diseases into HIV/AIDS treatment in Uganda. (19th June 2020) - Sando, David; Kintu, Alexander; Okello, Samson; Kawungezi, Peter Chris; Guwatudde, David; Mutungi, Gerald; Muyindike, Winnie; Menzies, Nicolas A; Danaei, Goodarz; Verguet, Stéphane
Abstract: Introduction: Despite growing enthusiasm for integrating treatment of non‐communicable diseases (NCDs) into human immunodeficiency virus (HIV) care and treatment services in sub‐Saharan Africa, there is little evidence on the potential health and financial consequences of such integration. We aim to study the cost‐effectiveness of basic NCD‐HIV integration in a Ugandan setting. Methods: We developed an epidemiologic‐cost model to analyze, from the provider perspective, the cost‐effectiveness of integrating hypertension, diabetes mellitus (DM) and high cholesterol screening and treatment for people living with HIV (PLWH) receiving antiretroviral therapy (ART) in Uganda. We utilized cardiovascular disease (CVD) risk estimations drawing from the previously established Globorisk model and systematic reviews; HIV and NCD risk factor prevalence from the World Health Organization's STEPwise approach to Surveillance survey and global databases; and cost data from national drug price lists, expert consultation and the literature. Averted CVD cases and corresponding disability‐adjusted life years were estimated over 10 subsequent years along with incremental cost‐effectiveness of the integration. Results: Integrating services for hypertension, DM, and high cholesterol among ART patients in Uganda was associated with a mean decrease of the 10‐year risk of a CVD event: from 8.2 to 6.6% in older PLWH women (absolute risk reduction of 1.6%), and from 10.7 to 9.5% in older PLWH men (absolute risk reduction of 1.2%), respectively. Integration would yield estimated net costs between $1, 400 and $3, 250 per disability‐adjusted life year averted among older ART patients. Conclusions: Providing services for hypertension, DM and high cholesterol for Ugandan ART patients would reduce the overall CVD risk among these patients; it would amount to about 2.4% of national HIV/AIDS expenditure, and would present a cost‐effectiveness comparable to other standalone interventions to address NCDs in low‐ and middle‐income country settings.